Unusual suspects? A group position approach to explaining anti-refugee attitudes among secular Turks. - Morgül, Kerem; Savaşkan, Osman (Journal of Ethnic & Migration Studies, 2025)
Why do Turkish majority members with a secular outlook exhibit above-average levels of antipathy toward Syrian refugees, despite their left-leaning political views and relatively cosmopolitan cultural dispositions? We address this question through a sequential mixed methods design, integrating focus group discussions and in-depth interviews conducted in Istanbul in late 2019 with an original survey of Istanbul residents fielded in July-August 2020. We find that secular Turks' attitudes toward Syrian refugees are entangled with the political and lifestyle threats they feel under President Erdoğan's increasingly authoritarian and Islamist regime. On one hand, secular citizens worry that Syrian refugees could shift the political balance in favor of Erdoğan, thereby further undermining the opposition's electoral prospects. On the other, they associate Syrian refugees with Turkey's growing estrangement from the West and the resulting decline in secularism and women's freedoms. Thus, secular Turks' animosity toward Syrian refugees does not stem merely from an aversion to religious traditionalism but reflects broader concerns about their own power and status in contemporary Turkey. Extending Blumer's group position theory, we argue that in deeply polarized societies, natives might view migrants through the lens of how these newcomers might affect their group's social position vis-à-vis other domestic groups.